2017
DOI: 10.1111/1742-6723.12808
|View full text |Cite
|
Sign up to set email alerts
|

Influenza‐associated delays in patient throughput and premature patient departure in emergency departments in New South Wales, Australia: A time series analysis

Abstract: Circulating influenza was associated with sustained increases and peaks in delayed patient throughput and premature patient departures. Influenza surveillance information may assist with development of health system and hospital workforce planning and bed management activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…One study found that 25% of ED visits during peak periods are for fever and respiratory infection symptoms [9]. Peak influenza circulation is associated with reduced ED throughput efficiency, increased ED length of stay (LOS), and a greater proportion of patients who depart before seeing a physician [10]. Additionally, influenza patients' median LOS is five times greater than other ambulatory ED patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that 25% of ED visits during peak periods are for fever and respiratory infection symptoms [9]. Peak influenza circulation is associated with reduced ED throughput efficiency, increased ED length of stay (LOS), and a greater proportion of patients who depart before seeing a physician [10]. Additionally, influenza patients' median LOS is five times greater than other ambulatory ED patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown increased emergency department stay lengths, bed use and premature patient departures during influenza epidemics. [35]…”
Section: Introductionmentioning
confidence: 99%
“…They are not generally used to forecast the severity of an emerging season and may not provide early warning for facilitating preparedness and surge capacity planning. Increased hospital and health system demand during the influenza season [8-10] is a high priority for health managers because influenza epidemics result in a surge of emergency department and hospital admissions [11-13].…”
Section: Introductionmentioning
confidence: 99%